International students’ experiences on speaking and writing skills in language learning processes in higher education - İsmail Karakuş (PLoS ONE, 2025)
Although speaking and writing skills play a crucial role in second language acquisition, studies focusing specifically on the challenges faced by international students learning Turkish as a foreign language remain limited. This study aims to explore the experiences of international students enrolled in higher education institutions in Turkey, particularly regarding the development of their speaking and writing skills in the context of Turkish language learning. Adopting a phenomenological design within a qualitative research framework, data were collected from 24 international students through semi-structured interviews and analyzed using content analysis. The findings revealed that students struggled with the pronunciation of certain sounds, maintaining fluency, organizing their thoughts coherently, expressing themselves accurately, applying grammar rules, and choosing appropriate vocabulary. Furthermore, participants reported experiencing anxiety about making mistakes, as well as various psychological barriers that hindered their ability to express themselves effectively. In terms of writing skills, the most prominent difficulties included grammatical errors, challenges in spelling vowels and specific consonants, misuse of punctuation, and slow writing speed. Students also indicated that their limited vocabulary and difficulties adapting to Turkish syntax negatively affected their writing performance. These findings underscore the need for integrated language instruction programs that simultaneously address speaking and writing skills, offering structured practice opportunities, anxiety-reducing strategies, and greater chances for meaningful interaction. The results provide valuable insights for language instructors, curriculum designers, and policymakers aiming to improve Turkish as a foreign language instruction tailored to the specific needs of international learners.